Cesarean childbirth in Brazil: prevalence, indications and risks entailed for the mother and child binomial (Research, Society and Development, 2022)
This study aimed to understand the reasons why cesarean section is the most performed type of delivery in Brazil. This is an integrative literature review, whose data collection was carried out in the Virtual Health Library (VHL) and its indexed sites, having as keywords, after checking the Health Sciences Descriptors website (DeCS): cesarean section, neonatal morbidity and mortality and women's health; using the connective “and” to join them. The research had as inclusion criteria: studies published in the last 10 years, available in Portuguese and English, which were available in full and were free of charge; being excluded: materials with a publication date prior to 2012, which were available in languages other than Portuguese and English, incomplete, duplicated and paid for. After full reading, 10 studies were selected, which were analyzed, grouped and organized into two categories of discussion: factors related to the high rates of cesarean sections in Brazil and risks of cesarean section compared to vaginal delivery. The findings demonstrate the disproportionality of the percentage of cesarean sections recommended by the WHO and the current, in Brazil, that there are several factors related to this, and that the risks of the dissemination of this practice are real, but underestimated. This reality shows that it is essential to reduce this percentage and, for that, it is necessary to adopt a more humanized care model, in which the empowerment and autonomy of women are encouraged, and the dissemination of information about the risks and benefits of women delivery pathways.